MEDIA SOSIAL SEBAGAI KONTEKS PENDIDIKAN KRISTIANI KONTEKSTUAL BAGI GENERASI MILLENNIAL - APRIANI M. SIBARANI (JURNAL ILMIAH MAKSITEK, 2020)
The advancement of science and technology plays a big role in the development of our society. The backlog in educationcan be calibrated through social media. As social media and millenials are inseparable, it is but proper to make use of socialmedia as an effective platform to curb the millenials’ Christian Education illiteracy. This article explores the utilitization ofsocial media as a double-edged tool to deliver a holistic Christian Education context right at their comfort. This articlerecommends Shared Christian Praxis (SCP) approach as a method to tailor Christian Education context for millennials insocial media context.